(3GdLaQ GdLGeY hGdfhQ GddGeYs - (3YHO GdQMef Hf eMeO Hf Ydj Hf CMeO Hf eMeO GdHSWGej GdMfaj, Rjf GdOjf,J (B858 (3g` s
(3ChdgG (B:s
(3GdMeO GdPi ChOY GdSQ GdecJhe ai Wi GdMQa GdeQbhe GYde habc Gddg Edi cTa SQg s
(3BNQgG (B:s
(3aCNPfG QHY GdcGa dCfgG OhQ GdKGdK, acGfJ g` acGf GdedbhW jchf Q g` S G f G N O Ge Q g`Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B184s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B231 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B323 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B152 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI HdOjI GdEScfOQjI (B(5240) s
Keywords: (3GdMQha h GdChaGbs